Intelligent building management system - Kerh, YiChuan. (2012)
Advancements in technology have led to renewed interest in the electric transportation infrastructure. Coupled with the depletion of fossil fuels in around the world, huge investments have been injected into developing low costs, highly reliable electric vehicles to replace those powered by fuel.